2022
DOI: 10.1001/jamapediatrics.2021.5038
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acute Kidney Injury During Diabetic Ketoacidosis With Risk of Microalbuminuria in Children With Type 1 Diabetes

Abstract: IMPORTANCE Diabetic kidney disease is among the most important causes of end-stage kidney disease worldwide. Risk factors for diabetic kidney disease remain incompletely defined. Recent studies document a high frequency of acute kidney injury (AKI) during diabetic ketoacidosis (DKA) in children, raising the question of whether these AKI episodes might contribute to future risk of diabetic kidney disease. OBJECTIVE To determine whether episodes of AKI occurring during DKA in children are associated with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 43 publications
1
27
0
2
Order By: Relevance
“…We also found that diabetes-related AKI was associated with race and ethnicity but not COI category. Although studies among adults with T1D have demonstrated racial differences in AKI 60 , 61 , 62 and recent work among children has highlighted the frequency of AKI in children with DKA, 19 , 20 , 21 , 22 no studies to our knowledge have explicitly studied the association between race and ethnicity and diabetes-related AKI risk in the pediatric population. Thus, our finding that race and ethnicity constituted a significant factor associated with AKI across all levels of COI is novel, and future research should focus on racial and ethnic disparities in AKI among children with DKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that diabetes-related AKI was associated with race and ethnicity but not COI category. Although studies among adults with T1D have demonstrated racial differences in AKI 60 , 61 , 62 and recent work among children has highlighted the frequency of AKI in children with DKA, 19 , 20 , 21 , 22 no studies to our knowledge have explicitly studied the association between race and ethnicity and diabetes-related AKI risk in the pediatric population. Thus, our finding that race and ethnicity constituted a significant factor associated with AKI across all levels of COI is novel, and future research should focus on racial and ethnic disparities in AKI among children with DKA.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes included the proportion of encounters with codes for AKI ( ICD-9 : 584.5-584.9 and 586; ICD-10 : N17.0-N17.2, N17.8, N17.9, and N19) or CE ( ICD-9 : 348.5; ICD-10 : G93.6) at the index visit. Acute kidney injury and CE were selected as secondary outcomes given the commonality of AKI 19 , 20 , 21 , 22 and the mortality associated with CE. 17 , 23 , 24 , 25 …”
Section: Methodsmentioning
confidence: 99%
“…The identification of T1DM patients who have developed an AKI episode is relevant for the planning of an accurate follow-up for renal function, microalbuminuria and blood pressure. For example, patients who developed an AKI at T1DM onset presented an increased risk of developing microalbuminuria during the follow-up [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in 2345 children having both type-1 diabetes and albuminuria demonstrated that the development of acute kidney injury is positively associated with the episodes of DKA [93]. A study that included 658 hospitalized patients with confirmed COVID-19…”
Section: Sars-cov-2 Infection Exacerbates Diabetes-induced Renal Comp...mentioning
confidence: 99%